Adolescent deliberate self‐poisoning in South‐East Melbourne. (1st October 2016) - Hiremath, Mandira; Craig, Simon; Graudins, Andis
Abstract: Objective: To describe the characteristics of adolescents presenting with deliberate self‐poisoning (DSP) to a large Australian healthcare network. Method: This is a retrospective chart review of 12–17 year olds presenting to three Monash Health EDs with self‐poisoning from January 2012 to December 2014. Results: There were 35 207 adolescent presentations in the study period. A total of 721 cases were for DSP (2%), and 501 (1.4%) presented with recreational or accidental self‐poisoning. The most common DSP toxicants were paracetamol (28%), non‐steroidal anti‐inflammatory agents (15%) and serotonin reuptake inhibitors (10%). Of the DSP presentations, 96% were impulsive events; 23% of patients ( n  = 129) presented on multiple occasions, and 67% of all DSP cases had a past psychiatric history, particularly depression (57%). Disposition for DSP patients included 60% discharged home, 6% short stay unit, 19% medical admission, 13% psychiatric admission and 2% intensive care unit admission. There were no mortalities. Conclusion: Adolescent DSP presentations frequently involved impulsive ingestion of over‐the‐counter medications, suggesting less access to prescription medications. Additionally, pre‐existing mental health history and re‐presentation were common. Initiatives to prevent DSP might include an increased focus on the early identification and management of mental health problems in adolescents in the community.